2003
DOI: 10.1023/a:1024422625596
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The ability of such bioactive excipients to simultaneously manipulate different cellular processes must be considered in selecting excipients for oral drug delivery systems. Such information is particularly relevant when the drug is lipophilic, a candidate for P-glycoprotein efflux, and where intestinal lymphatic targeting via chylomicron stimulation is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the present study, SLNs were fabricated using surfactant mixture composed of lecithin and poloxamer 188, and the ratio of lecithin to poloxamer 188 was fixed at 1:4 to achieve a small particle size. It has been reported that the presence of phospholipid on the shell layer of SLNs could increase the absorption and entrapment in microvilli because the phospholipid of soy lecithin is similar to the phospholipid bilayer structure of cellular membrane [30]. Formulation variables involved in the preparation of SLNs were optimized to achieve a smaller particle size (238 ± 10.9 nm) and high EE% (79 ± 2.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, SLNs were fabricated using surfactant mixture composed of lecithin and poloxamer 188, and the ratio of lecithin to poloxamer 188 was fixed at 1:4 to achieve a small particle size. It has been reported that the presence of phospholipid on the shell layer of SLNs could increase the absorption and entrapment in microvilli because the phospholipid of soy lecithin is similar to the phospholipid bilayer structure of cellular membrane [30]. Formulation variables involved in the preparation of SLNs were optimized to achieve a smaller particle size (238 ± 10.9 nm) and high EE% (79 ± 2.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Both Pluronic block copolymers L-81 and P-85 have been examined together in the same studies including lipid-Pluronic interactions [23], cellular uptake of proteins [24], and functional activity of multidrug resistance-associated proteins [25]. Both nonionic surfactants have also been shown to inhibit intestinal P-glycoprotein efflux [26, 27]. In this study, we investigated the effect of the inhibition of chylomicron formation by L-81 and P-85 on the secretion of GLP-1 and GIP, as well as the role of free fatty acids (FFA) on incretin release.…”
Section: Introductionmentioning
confidence: 99%
“…It also brings new opportunities for various excipients that are emerging as bioactive recently in the last decade [76]. Further, excipients such as Cremophor EL and pluronic polymers have been shown to decrease chylomicron production and reduce the P-gp efflux transport of drug molecules [77,78]. One of the versatile excipients in this category is tween 80 which has been found as excellent solubilizer, inhibitor of P-gp efflux and increase chylomicron production [76,79].…”
Section: Lymphatic Transport Of Lipid Carriersmentioning
confidence: 99%